Analysis of The Implementation of Revenue Cycle Accounting Information Systems in CV. Makassar Techniques: English - Aprilia, Alifia; Sahade; Samsinar (Muhasabatuna : Jurnal Akuntansi Syariah, 2023)
This study aims to find out how the implementation of the income cycle accounting information system at CV Makassar Teknik, so that the variable that is the focus of this scientific work is Income Cycle Accounting Information. The population in this study is the application of accounting information systems in the income cycle, while the samples in this study are reports of accounting information systems in the income cycle and supporting document data used by CV. Macassar Engineering. in 2022. The data collection techniques used were interviews, observation and documentation. The data analysis technique used is descriptive qualitative. The results showed that the application of accounting information systems to the income cycle at CV. Makassar Technique is still implemented in a very simple form so that it can still result in threats to the revenue cycle such as losses due to the absence of a company's personal account, evidence of transactions that are not stored properly, and unclear job descriptions due to a shortage of manpower. CV. Makassar Engineering needs to make various efforts to minimize threats to the revenue cycle, especially in accounting information systems, such as by starting to procure company financial reports.